(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
Nanomaterials have the potential to enable tremendous technological advancement, which is why they are attracting the attention of leading researchers at the moment. Nanocomposites based on transition metal oxides show great promise across a variety of fields and devices, including solar cells, photocatalytic degradation, supercapacitors, sensors, and bactericidal applications. Nanocomposites have been synthesized using a wide variety of methods, from simple chemical procedures to more complex methods such as Co-precipitation, sol-gel techniques, hydrothermal procedures, microwave-assisted synthesis, and biosynthesis. Nanoscale transition-metal oxide particles have been successfully fabricated using several analytical techniques, XRD, SEM, TEM, EDX, BET, TGA, IR, Raman, and UV spectroscopy are all included. Testing the utility of synthetic nanomaterials in solar, electrical, magnetic, and storage applications is the key action plan. In an effort to develop cleaner, more sustainable processes, scientists are currently studying the catalytic activity of nanocomposites in organic transformations. Nanocomposites based on transition metal oxides are reviewed in this article, along with their numerous morphologies, several characterization methods for identifying surface and structural properties, and their catalytic potential.